Sentidos de educação e educação matemática em disputa na política curricular em Mato Grosso : os professores de matemática e seus discursos - Gois, Eudes Arrais (2020)
This research presents the theme called a curricular policy to mathematics and part of the problematization of the prescriptive rationality ongoing in educational context, specifically in the educational state system of Mato Grosso. The interest context of this research has its historical constitution marked by the reformism that assists Brazil in the 90s. Due to the rising curricular control of the school via knowledge standardization attempts to be taught-learned, a series of questions became important: how is it understood the main terms of the policy to the mathematics teaching in the schools? How do teachers interpret the curricular centralization? How does the curricular development in mathematics occur? What sense of education and curriculum are produced in the school space in this process? In such a way, this investigation is oriented by the following question: how do the curricular development happen in a context of the expansion of curricular prescription? To this, the aim of this study is to understand how the mathematics curricular development takes place in the final years of the elementary school in a prescriptive growth context. In order to develop this investigation, some specific objectives were raised: 1. Investigating curriculum senses among mathematics’ teachers who work in schools of the state system; 2. Characterizing the dimensions of the mathematics´ teachers educational work not considered by the official policies; 3. Discussing the implications of producing curricular policy in mathematics at school in a prescriptive context. The research methodology is anchored in the autobiography, considering the subject's perspective as relational (MILLER; MACEDO, 2018), as well as, a theorization based on the comprehension of the curriculum as a cultural practice. Thus, the research takes the post-structural perspective of curriculum, anchored in researchers such as Elizabeth Macedo and Alice Casimiro Lopes, who discuss curriculum as a discursive practice, supported by Ernesto Laclau and Chantal Mouffe. To discuss about mathematics education, D’Ambrósio, Fiorentini e Lorenzato, Ortigão, Bicudo e Borba, David e Moreira, Valente, are the ones used as theoretical basis, especially because they are recognized authors who produce in the related area. Regarding empiricism, semi-structured interviews were developed with 04 (four) teachers who work in different schools of the educational state system of Rondonópolis (MT), having as instrument of research a semi-structured questionnaire; the research also relies on documentary analysis of curricular texts produced in the state of Mato Grosso. Regarding the analysis, the research empiricism, it is important to highlight that the curricular prescription disregards the school as a place of politics and politics, and, consequently, the curriculum centralization is not interesting by the perspective of improving the quality of education at school, as it has been commonly defended by the educational reformers. Tensioning such discussion in the curricular field, I assume the curriculum as a text, a practice of meaning, which the curriculum is an integral part of school life, but also it is developed by a series of external actors.